2016
DOI: 10.3892/ol.2016.5315
|View full text |Cite
|
Sign up to set email alerts
|

EMT influences the expression of CK19 in pleural effusion-derived lung cancer cells and their invasion and metastasis

Abstract: Lung cancer is the most common cancer after breast and colon cancer, with high rates of mortality, worldwide. There are two main types of lung cancer, small cell lung carcinoma (SCLC), which accounts for approximately 20% of all lung cancer cases and non-SCLC, which accounts for almost 80% of lung cancer cases. Although lung cancer is one of the most aggressive types of cancer, progress in achieving better clinical outcomes has been gradual. Even though a number of markers have been suggested for the diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…2nd day n = 12, 4th day n = 12, each MOI n = 6 and control n = 6. 19 . Therefore, downregulation of CK19 refers to lose in structural integrity of epithelial cell.…”
Section: Discussionmentioning
confidence: 99%
“…2nd day n = 12, 4th day n = 12, each MOI n = 6 and control n = 6. 19 . Therefore, downregulation of CK19 refers to lose in structural integrity of epithelial cell.…”
Section: Discussionmentioning
confidence: 99%
“…EMT is a process by which epithelial cells are transformed into mesenchymal cells, and plays an important role in invasion and migration during cancer metastasis. 15 Kim et al also reported that EMT is possibly involved in acquired resistance to crizotinib in vitro. 16 In general, morphological change to spindle cell shape is accompanied by a decrease in E-cadherin and an increase in vimentin, and an overexpression of vimentin predicts the progression and an unfavorable survival in NSCLC.…”
Section: Discussionmentioning
confidence: 98%
“…EMT is a process by which epithelial cells are transformed into mesenchymal cells, and plays an important role in invasion and migration during cancer metastasis . Kim et al also reported that EMT is possibly involved in acquired resistance to crizotinib in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…EMT is reactivated during adulthood under conditions of disease, such as cancer. EMT determines the severity of cancer and contributes to metastasis [ 5 ]. EMT is a progressive malignant cell program that enhances the mobility, invasion, resistance to apoptotic stimuli, and therapeutic resistance of cancer cells [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cytokeratins (CKs) are cancer biomarkers and are the main structural elements of the cytoskeleton in epithelial cells. CK19 is expressed in the epithelium covering the bronchial tree and is overexpressed in lung cancer [ 5 ]. Conflicting information on the relationship between ADA and cancer has been reported in previous studies, some of which have found ADA activity to be increased in malignant tissues and others of which have found it to be decreased [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%